[Mailman on Bicycle] - (:unkn) unknown (My University, 2010)
A mailman in uniform, with sack of mail, riding through the streets on his bicycle. The building with overhanging veranda at the mailman's right, whose sign reads "Hotel", is the La India Hotel, located in Port of Spain, Trinidad.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Streets--Trinidad and Tobago; Children--Trinidad and Tobago; Bicycles--Trinidad and Tobago; Letter carriers--Trinidad and Tobago; Postal service--Employees; Clothing and dress--Trinidad and Tobago; Uniforms--Trinidad and Tobago; Pedestrians--Trinidad and Tobago; Architecture--Trinidad and Tobago; Wrought-iron--Trinidad and Tobago; Hotels--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Signs and signboards--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Bars (Drinking establishments)--Trinidad and Tobago; Billiard parlors--Trinidad and Tobago; Hotel restaurants--Trinidad and Tobago; Restaurants--Trinidad and Tobago